2010
DOI: 10.1007/s11064-010-0322-0
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of the Serine Protease Omi/HtrA2 from Mitochondria into the Cytosol Upon Seizure-Induced Hippocampal Injury in the Neonatal Rat Brain

Abstract: Omi/HtrA2 is a pro-apoptotic mitochondrial serine protease involved in caspase-dependent as well as caspase-independent cell death upon various brain injuries. However, the role of Omi/HtrA2 in neuronal death induced by status epilepticus (SE) in the immature brain has not been reported. In this study, we analyzed the contribution of serine protease Omi/HtrA2, its substrate X-linked inhibitor of apoptosis protein (XIAP) and the caspase-3 activation to damage of hippocamplal CA1 cells following lithium-pilocarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In contrast, we found that neurons located in the ischemic core display necrotic cell death. We have reported in our previous study that Omi/ HtrA2 was specifically upregulated in the penumbra and translocated from mitochondria to cytosol after cerebral ischemia as well as after epilepsy in rats [25,26]. In the present study we demonstrated an up-regulation of HtrA2 in the penumbra after focal ischemia which was accompanied by a parallel down-regulation of the antiapoptotic protein HAX-1.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In contrast, we found that neurons located in the ischemic core display necrotic cell death. We have reported in our previous study that Omi/ HtrA2 was specifically upregulated in the penumbra and translocated from mitochondria to cytosol after cerebral ischemia as well as after epilepsy in rats [25,26]. In the present study we demonstrated an up-regulation of HtrA2 in the penumbra after focal ischemia which was accompanied by a parallel down-regulation of the antiapoptotic protein HAX-1.…”
Section: Discussionsupporting
confidence: 72%
“…We have previously reported that focal ischemia results in Omi/HtrA2 accumulation in the cytosol, where it probably promotes neuronal death by neutralizing and cleaving XIAP, one of the most potent endogenous inhibitors of apoptosis [25,26]. In the present study, we sought to determine whether (1) HAX-1 expression is altered in brains subjected to focal cerebral ischemia; (2) and if so, to investigate whether this alteration correlated to HtrA2-redistribution and execution of neuronal death.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, we should keep in mind that HAX-1 is not the only antiapoptotic protein that is cleaved and inactivated by HtrA2 during apoptotic cell death. For instance XIAP, the most potent endogenous inhibitor of apoptosis, can itself undergo protease-mediated breakdown after SE [15]. As matter of fact, it has been recently shown that the interaction between HAX-1 and XIAP blocks polyubiquitination of XIAP [26].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that upon apoptosis stimulation, the formation of HAX-1-XIAP complex increases the stability of XIAP by suppressing its ubiquitination, and thus the stabilized complex attenuates apoptosis by inhibition of caspase-9 activation. However, seeing that XIAP is also cleaved by HtrA2 following SE and cerebral ischemia [15,27], we can assume that the HAX-1-XIAP complex does not function correctly. In this regard, a very interesting question is whether HAX-1 is involved in caspase-independent cell death in either pathophysiological or physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation